2005
DOI: 10.1002/prep.200500006
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Dynamic Response of Thermocouples in Inert and Reacting Condensed Phase Energetic Materials

Abstract: Thermocouples are widely used to measure both transient and steady state temperatures in many different materials. Bead diameters range from a few micrometers to several millimeters. During steady state operations, dynamic response is not an issue. However, during fluctuating conditions, the temporal response of the thermocouple must be taken into account. Several different techniques have been developed to measure the response characteristics of measurements in inert gases and liquids, but to the authors know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The Beltrami equations in (6) in metric (15) have the form (16) where . The inverted Beltrami equations in metric tensor (15) are written as (17) where (18) Diffusion equations (8) in metric (15) are given by (19) Therefore, in this metric, the inverted diffusion equations required for adaptive grid generation in have the form…”
Section: Inverted Beltrami and Diffusion Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Beltrami equations in (6) in metric (15) have the form (16) where . The inverted Beltrami equations in metric tensor (15) are written as (17) where (18) Diffusion equations (8) in metric (15) are given by (19) Therefore, in this metric, the inverted diffusion equations required for adaptive grid generation in have the form…”
Section: Inverted Beltrami and Diffusion Equationsmentioning
confidence: 99%
“…Grounded thermocouple sensors find wide applications in various engineering devices used to measure heat fluxes in complex heat stressed structures [14], various heat exchange devices [15], and in the burn ing of unitary solid fuel [16][17][18]. In this case, the problem arises of estimating the reliability of quantities derived from thermocouple measurements.…”
Section: Adaptive Grid Generation Near Curves and Surfacesmentioning
confidence: 99%
“…Laser heating measurements of these thermocouples in air and in water give a response time of between 1.5 and 10 ms depending on the thermal conductivity of the surrounding medium [33,34]. This range is used to deconvolve the temperature measurements in the ignition volume and back out actual HE temperatures.…”
Section: Small-scale Instrumented Thermal Ignition Experimentsmentioning
confidence: 99%
“…Conclusions (1) Numerical simulation has revealed the presence of a considerable error in temperature measurement in SP with the use of a thermocouple. The magnitude of this error depends both on the burning rate and the size of the thermocouple junction.…”
mentioning
confidence: 97%
“…Unfortunately, this fact was not properly attended for a long time and the error estimates for temperature measurements by thermocouples are quite contradictory. There are just a few studies [1][2][3] considering this problem. Therefore, in this paper we study the indicated heat exchange processes with the use of numerical simulation and give estimates of possible errors in temperature measurement in SP by thermocouples.…”
mentioning
confidence: 99%